Transcriptomics in the wild: Hibernation physiology in free‐ranging dwarf lemurs. Issue 3 (29th January 2018) - Faherty, Sheena L.; Villanueva‐Cañas, José Luis; Blanco, Marina B.; Albà, M. Mar; Yoder, Anne D.
Abstract: Hibernation is an adaptive strategy some mammals use to survive highly seasonal or unpredictable environments. We present the first investigation on the transcriptomics of hibernation in a natural population of primate hibernators: Crossley's dwarf lemurs ( Cheirogaleus crossleyi ). Using capture–mark–recapture techniques to track the same animals over a period of 7 months in Madagascar, we used RNA‐seq to compare gene expression profiles in white adipose tissue (WAT) during three distinct physiological states. We focus on pathway analysis to assess the biological significance of transcriptional changes in dwarf lemur WAT and, by comparing and contrasting what is known in other model hibernating species, contribute to a broader understanding of genomic contributions of hibernation across Mammalia. The hibernation signature is characterized by a suppression of lipid biosynthesis, pyruvate metabolism and mitochondrial‐associated functions, and an accumulation of transcripts encoding ribosomal components and iron‐storage proteins. The data support a key role of pyruvate dehydrogenase kinase isoenzyme 4 ( PDK4 ) in regulating the shift in fuel economy during periods of severe food deprivation. This pattern of PDK4 holds true across representative hibernating species from disparate mammalian groups, suggesting that the genetic underpinnings of hibernation may be ancestral to mammals.